White spot lesions: Resin infiltration technique - Hilda SARKIS; Maroun GHALEB; Sarah DABBAGH; Elie HAROUNY (International Arab Journal of Dentistry (IAJD), 2017)
Nowadays, dentists are facing increased aesthetic demands from patients. Corrections of shade, shape, texture and position are the most requested. The shade of the teeth is a very important concern for patients, especially when white spots cover a big part of their front teeth. On the other hand, all of the focus in the last fewyears has been to create more conservative techniques to solve this problem. Erosion/infiltration protocol using Icon (DMG, Hamburg, Germany) is one of the most conservative and efficient protocols. The Icon treatment was initially proposed as a simple and minimally invasive alternative for caries treatment of initial proximal lesions, but surprisingly the technique proved a high ability to mask the white spots by modifying the refractive index of the lesion. The aim of this article isto describe this technique in detail using a clinical case.